2019
DOI: 10.1186/s10397-019-1055-y
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic exenteration in gynecologic cancer: complications and oncological outcome

Abstract: Introduction: Pelvic exenteration (PE) is indicated in cases of unresponsive, recurrent pelvic cancer or for palliative intent. Despite the fact that the surgery is associated with a high rate of morbidity, it is currently the only real option that can effect a cure. Material and methods: Patients who underwent PE between January 2011 and July 2017 in our centre were retrospectively reviewed. Data related to surgery, complications and outcomes were recorded. Results: Twenty-three patients were included. PE was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…Recently, Lago et al published a retrospective study including patients who underwent pelvic exenteration with incontinent urinary and/or digestive reconstruction for gynecologic malignancies, and found a rate of grade III–IV complications according to the Clavien-Dindo classification of 48%, in line with our results. In agreement with our study, they observed a similar rate of urinary and digestive complications (approximately 17% and 26%, respectively) 20. Four previous studies have compared the rate of complications between continent and incontinent urinary diversion in patients with gynecologic cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Lago et al published a retrospective study including patients who underwent pelvic exenteration with incontinent urinary and/or digestive reconstruction for gynecologic malignancies, and found a rate of grade III–IV complications according to the Clavien-Dindo classification of 48%, in line with our results. In agreement with our study, they observed a similar rate of urinary and digestive complications (approximately 17% and 26%, respectively) 20. Four previous studies have compared the rate of complications between continent and incontinent urinary diversion in patients with gynecologic cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Despite preoperative assessment, patients undergoing TPE are at higher risk for postoperative complications. Most studies reported approximately 44.0-80.0% prevalence of various postoperative complications after TPE [3][4][5][6][7][8], with infectious complications accounting for 10 to 23% [2,3]. However, in some studies, in a selected group of patients, infections were as high as 40-50.0% [6,9] as a result of overlapping of multiple risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary and fecal diversion is needed to restore normal function after total pelvic exenteration because of gynecological cancer. 1 In these patients, the Bricker procedure and end colostomy are often used for this purpose. Nevertheless, their use may lead to complications in patients with previous radiotherapy and may influence the ileum anastomosis.…”
mentioning
confidence: 99%
“…During the postoperative period, several studies have demonstrated there is no statistically significant difference in the rate of postoperative complications such as stenosis of the uretero-intestinal anastomosis, obstructive nephropathy, formation of calculi in the conduit, urinary infections or electrolyte imbalances (Table 1). [1][2][3][4] The urine drains into a reservoir distal to the stoma; consequently, the mixture of fecal content with urine and the resultant Video article ascending pyelonephritis is greatly reduced. Furthermore, with adequate stoma care and regular change of collection appliances, peristomal dermatitis and other local skin complications can be avoided or easily controlled.…”
mentioning
confidence: 99%
See 1 more Smart Citation